Teaching novices the handstand: a practical approach of different sport-specific feedback concepts on movement learning - Rohleder, J.; Vogt, T. (Science of Gymnastics Journal, 2018)
Due to rare evidence-based implications for the application of augmented feedback in gymnastics teaching, this study investigated whether standardised tactile-verbal feedback vs. visual-comparative feedback short-term enhance novel gymnasts` handstand postural performance and motor imagery. Twenty-six students (7 females, 19 males) were randomly assigned to the tactile-verbal feedback (age: 22.7 ± 3.9 years) or visual-comparative feedback (age: 21.9 ± 1.8 years) group (each n = 13), performing a pre-post designed experimental session of handstand trials. Conducting goniometric analyses for hip, shoulder and head position, feedback effects were monitored using video capture and a motion-doll. Shoulder positioning enhanced after receiving tactile-verbal feedback (p < .01), whereas shoulder angle imagery enhanced following visual-comparative feedback (p < .05). Furthermore, significant correlations between postural performance and motor imagery were found for head position after receiving tactile-verbal feedback (p < .01), whereas hip angle postural performance and motor imagery correlated significantly following visual-comparative feedback (p < .01). Tactile-verbal feedback and visual-comparative feedback effect several issues of motor learning in different manners; however, this is true even in a short-term approach. Thus, practical recommendations are suggested to consider combined feedback concepts to allow comprehensive handstand acquisition.